ANALISIS DANA DESA SULAWESI TENGGARA TAHUN 2016-2019 - Sulastri , Susi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This study aims to identify and analyze the magnitude of the development and contribution of village funds as a result of reforms in the formulation of village funds in Southeast Sulawesi in 2016-2019. This study uses secondary data from the Directorate General of Fiscal Balance. The data includes population data per sub-district, basic allocation per village and district from 90 percent to 77 percent, affirmative allocation data, data on formulation allocations of 10 percent, and data on the amount of village funds in Southeast Sulawesi for 2016-2019. The analytical tool used is descriptive quantitative analysis. The results showed that the development of village funds from 90 percent to 77 percent. In 2018 the amount of village funds will be reduced by Rp. 201,473.903 billion with the development of village funds decreased by around Rp. 9.20 percent. In 2017 the amount of village funds increased by Rp. 252,332,522 billion with a contribution of around 17.03 percent. In 2018 the amount of village funds will be reduced by Rp. 225,016,754 billion with the contribution of village funds decreased by 15.91 percent. In 2019 the amount of village funds will increase again by Rp. 251,213,678 billion with a village fund contribution of around Rp. 15.57 percent.